The function of serine/threonine-specific protein kinases in B cells - Han, Zhennan; Benlagha, Kamel; Lee, Pamela; Park, Chan-Sik; Filatov, Alexander; Byazrova, Maria G.; Miller, Heather; Yang, Lu; Liu, Chaohong (Frontiers in Immunology, 2024)
The serine/threonine-specific protein kinases (STKs) are important for cell survival, proliferation, differentiation, and apoptosis. In B cells, these kinases play indispensable roles in regulating important cellular functions. Multiple studies on human and other animal cells have shown that multiple STKs are involved in different stages of B cell development and antibody production. However, how STKs affect B cell development and function is still not completely understood. Considering that B cells are clinically important in immunity and diseases, our understanding of STKs' roles in B cells is in great need of investigation with current technologies. Investigating serine/threonine kinases will not only deepen our insight into B cell-related disorders but also facilitate the identification of more effective drug targets for conditions like lymphoma and systemic lupus erythematosus.